2014
DOI: 10.1371/journal.pone.0094230
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Liming on Health and Growth of a Masson Pine Stand Damaged by Soil Acidification in Chongqing, China

Abstract: In the last decades, the Masson pine (Pinus massoniana) forests in Chongqing, southwest China, have increasingly declined. Soil acidification was believed to be an important cause. Liming is widely used as a measure to alleviate soil acidification and its damage to trees, but little is known about long-term effects of liming on the health and growth of declining Masson pine forests. Soil chemical properties, health condition (defoliation and discoloration), and growth were evaluated following application of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 61 publications
(48 reference statements)
2
13
0
Order By: Relevance
“…Quicklime is conventionally applied to increase the soil pH, enhance the mobilization of nutrient ions and reduce the toxic effect of heavy metal ions (Li et al ., ). We observed a significant increase in the soil pH but little impact on the nutrient content after quicklime treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Quicklime is conventionally applied to increase the soil pH, enhance the mobilization of nutrient ions and reduce the toxic effect of heavy metal ions (Li et al ., ). We observed a significant increase in the soil pH but little impact on the nutrient content after quicklime treatment.…”
Section: Discussionmentioning
confidence: 98%
“…In China, the exponential increase of reactive nitrogen (N) input into the biosphere since the 1970s has likely led to more carbon (C) being sequestered in the biosphere (Cui et al, 2013;Shi et al, 2015). However, enhanced emissions of N 2 O and CH 4 due to chronic N pollution potentially offset the cooling effect by C sequestration (Liu and Greaver, 2009;Tian et al, 2011). Microbial nitrification and denitrification in soils account for about 60 % of N 2 O emissions globally (Ciais et al, 2013;Hu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Oh et al (2006) also found that calcium cyanamide was effective in stopping soil acidification in tea fields (with an initial pH of 4.5) when applied at almost the same rate as in our study. In traditional liming treatments in China, a large amount of burnt limestone powder (49.5% CaO, usually applied at greater than 2000 kg$ha -1 ) is recommended to obtain increased soil pH (Li et al, 2014). The burnt limestone powder in China is usually not granulated, combined with often humid weather, may result in a proportion of the calcium oxide (CaO) reacting with water (H 2 O) and carbon dioxide (CO 2 ) to produce calcium bicarbonate (CaHCO 3 ).…”
Section: Discussionmentioning
confidence: 99%